2013
DOI: 10.1016/j.ygyno.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Serial sectioning of the fallopian tube allows for improved identification of primary fallopian tube carcinoma

Abstract: Objective Serial sectioning of the fallopian tube in women undergoing risk reducing surgery has been shown to increase the detection rate of occult malignancy in BRCA mutation carriers. We undertook this study to determine whether this protocol at the time of surgery for ovarian cancer (OV) or primary peritoneal malignancies (PP) changes the detection rate of fallopian tube carcinoma (FT). We secondarily investigated where this difference affects patient outcomes. Methods A retrospective review of 130 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…There is support for both hypotheses from animal models 54 59 . However, aside from the investigation of STICs, distinct biologic, clinical or molecular features capable of categorical differentiation between the two have not yet been identified 60 . Our proteomics results now suggest a potential new level of simple stratification in HGSOC into mesenchymal and epithelial subtype HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…There is support for both hypotheses from animal models 54 59 . However, aside from the investigation of STICs, distinct biologic, clinical or molecular features capable of categorical differentiation between the two have not yet been identified 60 . Our proteomics results now suggest a potential new level of simple stratification in HGSOC into mesenchymal and epithelial subtype HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…Serial sectioning of the fallopian tube and intraoperative frozen section have been reported to be effective in identifying the disease. 24,25 In our series, 72.6% of those undergoing intraoperative frozen section were accurately diagnosed as PFTC, with 12.6% as ovarian cancer and 11.6% of adnexal neoplasm (undetermined primary neoplasm from either fallopian tube or ovary). The negative rate accounted for 3.0%, ensuring that 26 have reported that grade was a significant prognostic factor for patients with PFTC, others failed to establish such association.…”
Section: Discussionmentioning
confidence: 65%
“…Evidence to support the origination of “ovarian” cancer from the fallopian tube include the following; STICs have been seen in approximately 5-15% of women with germline mutations, such as BRCA 1/2 , that place them at increased risk of developing ovarian carcinomas (89, 107-109); when the fallopian tubes of women with advanced ovarian cancers are closely examined by SEE-FIM, STIC are detected in 50–60% of cases (110); identical TP53 mutations have been seen in STICs and adjacent high grade serous ovarian carcinomas, which suggests a clonal relationship (111, 112); and the molecular expression of high grade serous carcinomas more closely resembles that of the fallopian tube than the ovarian surface epithelium (8, 106). …”
Section: Surgical Prevention For Women At High Risk Of Ovarian Cancermentioning
confidence: 99%